Reappraisal of liver resection as an alternative to transplantation in locally advanced hepatoblastoma: a systematic review and analysis of pooled individual patient data - Fuchs, Juri; Rabaux-Eygasier, Lucas; Ruping, Fabian; Kessler, Markus; Günther, Patrick; Hoffmann, Katrin; Czigány, Zoltán; Michalski, Christoph; Hery, Geraldine; Mehrabi, Arianeb; Branchereau, Sophie (Pediatric blood & cancer, 2024)
Background There is ongoing debate regarding liver transplantation (LT) versus liver resection (LR) for locally advanced hepatoblastoma. However, comparative studies are lacking. Consequently, a significant evidence gap persists, hindering the establishment of consensus guidelines. This study aimed to compare LT and LR for locally advanced hepatoblastoma, using predefined inclusion criteria to ensure comparable intervention groups. Methods According to current Children's Oncology Group (COG) and SIOPEL (European Childhood Liver Tumour Study Group) recommendations, hepatoblastoma that requires LT evaluation was defined as either PRETEXT (PRE-Treatment EXTent of tumor) IV F+, POST-TEXT (POST-Treatment EXTent of tumor) IV, POST-TEXT P+, and/or POST-TEXT V+. A systematic literature search (Medline/Web-of-Science/Embase) was performed. Only patients who met the aforementioned criteria were included. Patient data were extracted individually and pooled. Results A total of 189 patients with locally advanced hepatoblastoma from 55 studies met the specified criteria, with 111 undergoing LT and 78 LR. There were no significant differences between the two groups in age, alpha-fetoprotein (AFP), and PRETEXT stages. Local recurrence was more common after LR (14% vs. 3% in LT, p = .008), while distant recurrence was more often observed after LT (16% vs. 5% in LR, p = .035). Overall survival (OS) and event-free survival (EFS) did not differ significantly between LT and LR (5-year OS: LT = 75.3% [95% confidence interval: 66.5-85.2], LR = 87.6% [80.4-95.6], p = .140; 5-year EFS: LT = 68.5% [59.3-79.1], LR = 71.1% [60.7-83.3], p = .700). Conclusion Real-life data revealed that a considerable number of patients with locally advanced hepatoblastoma underwent LR. This analysis suggests that outcomes are similar and favorable for both approaches. LR can therefore be considered an effective alternative to LT in selected cases even in locally advanced hepatoblastoma.
Gesehen am 27.03.2025